Analysis of the Potential Horticultural Products in Blitar Regency on the Agribusiness Market in Blitar Regency - Wicaksono, Karuniawan Puji; Permanasari, Paramyta Nila; Saitama, Akbar (International Journal of Environment, Agriculture and Biotechnology, 2023)
Blitar Regency has a wholesale market managed by the Wlingi Market Association, but some horticultural products from the farmers are still absorbed by the wholesale market outside Blitar Regency and reabsorbed by the retailers from Blitar Regency. Objectives of the research were to obtain information about the superior products, supply chain, and the inhibiting factors on the development of the horticultural products. Method of the research used descriptive analysis on each member of the links. Location of the research is the wholesale market in Blitar Regency, Wlingi. Variables of the research include types, volumes, and circulation of the horticultural products. Results of the research showed 3 major horticultural commodities that include chili, red pepper, and watermelon. The potential agricultural products in Blitar Regency have inefficient and complex supply chain because they involve many actors from farmers to consumers. The inhibiting factors are as follow: 1. The farmers do not have a collective system for marketing their crops so that information about the products as well as the prices are not integrated, 2. The supply chain patterns are inefficient and complex, so that the prices are costly, and 3. Inadequate location of the wholesale market. It is expected that the approach of supply chain on horticultural commodities in Blitar Regency will provide an overview of potential commodity supply availability as a consideration for supply chain management.